Aspects of Victimology in Legal Protection for Victims of Grooming - Pakaya, Arista (Universitas Negeri Gorontalo, 2025)
This study aims to determine what forms of legal protection are available for victims of criminal acts of ganging up when viewed from the victimology aspect. This study uses the research method normative conducted by reviewing legal facts in the field as well as theories, concepts, laws and so forth related to this research. The results of the study indicate that victim protection must be given both physical suffering and losses to their property as intended by the Victimology study by considering the elements contained in the criminal act of assault in the Criminal Code. In the concept of the principle of benefit, the principle of justice, the principle of balance and the principle of legal certainty which demands that all forms of protection must be provided fairly and in balance which guarantees legal certainty.